Pengaruh Ukuran Kantor Akuntan Publik (KAP), Ukuran Perusahaan Dan Opini Audit terhadap Auditor Switching - Ridho Wardana; Auliffi Ermian Challen (Majalah Sainstekes, 2018)
The aim of this study is to examine the influence of Audit Firm Size, Firm Size, and Audit Opinion towards Auditor Switching. Some of past research regarding auditor switching, shows different results. Because of that, another research needs to be done to verify theory of auditor switching. The purpose of this research is to find empirical proof concerning factors that might influence auditor switching in Indonesia.This research used the sample of real estate and property industries which listed in Indonesian Stock Exchange during 2010-2014 periods. The number of real estate and property industries sampled in this study were 10 companies with 5 years observation. Based on purposive sampling method, sample consist of 50 financial statements in this research. Research variable being used are Audit Firm Size (KAP), Firm Size (LnTA), Audit Opinion (OPINI), and Auditor Switching (SWITCH). By using logistic regression in SPSS 20 software. The result of this research shown below: (1) Audit Firm Size has effect on Auditor Switching, (2) Firm Size does not has effect towards Auditor Switching, and (3) Audit Opinion does not has effect towards Auditor Switching.